Complete NMR assignment and conformational analysis of 17‐α‐ethinylestradiol by using RDCs obtained in grafted graphene oxide. (11th October 2016) - França, José A. A.; Navarro‐Vázquez, Armando; Lei, Xinxiang; Sun, Han; Griesinger, Christian; Hallwass, Fernando
Abstract: The 1 H and 13 C NMR spectra of 17‐ α ‐ethinylestradiol (EE2 ), a well‐known contraceptive, including diastereotopic methylene groups, were fully assigned with the help of residual dipolar couplings (RDC) measured in the recently developed grafted graphene oxide orienting medium. RDC analysis, which included all 1 D CH couplings and the long‐range 2 D CH 1 H―C≡ 13 C coupling, also pointed to the presence of a minor conformation arising from pseudo‐rotation of the steroid B ring. Saturation‐transfer difference (STD) measurements revealed that the most likely interaction betweenEE2 and orienting medium occurred on the C and D ring. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : 1 H‐NMR and 13 C‐NMR spectra of 17‐α‐ethinylestradiol (EE2 ) were fully assigned with the help of RDC measured in grafted graphene oxide. RDC analysis ( 1 D CH and 2 D CH ) pointed to the presence of a minor conformation arising from pseudo‐rotation of the steroid B ring. STD measurements revealed that the most likely interaction betweenEE2 and orienting medium occurred on the C and D ring.